Desarrollo de una aplicación software para apoyar el proceso de gestión del mantenimiento preventivo de los equipos biomédicos del Hospital Susana López de Valencia E.S.E. (2021)
This research and development project focuses on the process of systematizing preventive maintenance of biomedical equipment at the Hospital Susana Lopez de Valencia E.S.E. (HSLV), from the city of Popayan (Cauca), with a focus on the pediatric intensive care area (PICU) .To this end, a software was developed and implemented for the management of preventive maintenance protocols for the biomedical equipment of the hospital, thus seeking the optimization of physical and economic resources, guaranteeing the reliability and consistency of the process and its information. This project is located within the line of work of Clinical Engineering as a graduate work project (TIG) for biomedical engineering. It was developed with the CDIO methodological approach (Conceive, Design, Implement and Operate), as a result of the execution of this project, two software tools were obtained: a mobile App and a desktop App through a development environment in Android studio for the mobile App and google sheets for the desktop App, which were validated through two tests: The first test was carried out with the help of the engineers in charge and the second was a satisfaction survey of the development of the applications; Despite being a prototype conceived for the HSLV PICU, it is a 100% functional system and scalable to any other hospital service. Through its architecture, this tool will be able to document management of the preventive maintenance process of biomedical equipment that is currently carried out manually on printed material.